Law, Human Capital and the Emergence of Free City-States in Medieval Italy - Marianna Belloc; Francesco Drago; Roberto Galbiati (Center for Economic Studies and ifo Institute (CESifo), 2017)
In this paper, we study how the birth of the first universities in Italy affected the emergence of the Italian free cities-states (the commune) in the period 1000-1300 a.d. Exploiting a panel dataset of 121 cities, we show that after the foundation of a new university the distance between each city in the sample and the university negatively predicts the timing of the birth of communal institutions in the city. Our evidence is consistent with the idea that universities in the Middle Ages provided the necessary juridical knowledge and skills to build legal capacity and develop broader-based institutions.
Keywords: I20; I23; K00; N33; 330; institutional change; education; human capital accumulation; communal movement